The relationships between pre- to syn-Pampean orogeny metasedimentary rocks in the Eastern sierras Pampeanas (Argentina) - Casquet, C. (2014)
Fil: Casquet, C. Universidad Complutense. Instituto de Geociencias. Departamento de Petrología y Geoquímica; España.